Immunostimulation by starch hydrogel-based oral vaccine using formalin-killed cells against edwardsiellosis in Japanese eel, Anguilla japonica. Issue 22 (8th May 2020) - Jun, Jin Woo; Kang, Jeong Woo; Giri, Sib Sankar; Yun, Saekil; Kim, Hyoun Joong; Guen Kim, Sang; Kim, Sang Wha; Han, Se Jin; Kwon, Jun; Oh, Woo Taek; Park, Se Chang
Highlights: Edwardsiellosis causes significant losses in Japanese eel aquaculture. Antibiotics or injection/immersion vaccines show limited effectiveness. Starch hydrogel oral (SHO) vaccines were superior to formalin-killed cell vaccines. Repeat SHO vaccination improved effectiveness, up to four days. Abstract: Edwardsiellosis outbreaks cause significant losses in Japanese eel aquaculture. The causative agent, Edwardsiella tarda, is an intracellular pathogen, and the use of antibiotics has a limited effectiveness. As Japanese eels are sensitive to stress, injection vaccines are not recommended for treatment; immersion methods are less stressful, but not cost-effective. Alternatively, oral vaccination methods are more promising. The aim of this study was to develop a starch hydrogel-based oral (SHO) vaccine against edwardsiellosis in Japanese eel, using formalin-killed cells. To assess the protective effect, we compared SHO vaccine with the conventional formalin-killed cell (FKC) vaccine. A bacterial agglutination test showed that agglutination titers in SHO-vaccinated group were higher than in the FKC-vaccinated group. Japanese eel survival rate (%) was monitored after challenge by E. tarda at four weeks post-vaccination. Survival rates in the FKC group (60%, first trial; 70%, second trial) were lower than in SHO groups. Percentage survival rates in three SHO groups (first and second trials, respectively) were as follows: 70% and 80% in the group vaccinated once per day for one day; and 80% and 90% in both groups vaccinated for four and eight days. Additionally, a boost SHO vaccination at 46 days prompted a similar or even higher protection against edwardsiellosis than after the initial vaccination. Both FKC and SHO vaccination upregulated levels of pro-inflammatory cytokines (interleukin (IL)-6, tumor necrosis factor (TNF)-α), and host defense cytokine (interferon (IFN)-α) in all immunized groups of fish when compared with the control. These results reveal the immunostimulation effect of SHO vaccine in Japanese eel, emphasizing its potential as an oral vaccine in aquaculture.